Retracted: Some Results for Periodic Solutions of a Kind of Liénard Equation - of Function Spaces, Journal (Journal of function spaces, 2020)
Journal of Function Spaces has retracted the article titled “Some Results for Periodic Solutions of a Kind of Liénard Equation” [1], due to significant overlap with a previous publication [2] without citation.